2021
DOI: 10.5897/jmer2021.0543
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mathematical model to study the impact of state of charge dependent exchange current density on the generated voltage hysteresis of silicon anode-based lithium half cells

Abstract: In this work, three different types of Silicon (porous, nano and bulk) anode-based coin cells are manufactured and lithiation-delithiation battery cycling tests are conducted. During the experiment, a capacity difference is witnessed at the beginning and the end point of the battery cycling loop. This capacity difference during battery cycling is reduced by implementing side-reaction correction technique on the exchange current density using Tafel kinetics formula. A huge voltage gap known as voltage hysteresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In case of ๐›บ, constant values were used throughout the lithiation-delithiation cycling. Some impacts from ๐›บ were seen, but this parameter is also connected with diffusivity as reported by various researchers at their work (Verbrugge et al, 2015;Verbrugge and Cheng, 2019;Sethuraman et al, 2010;Sethuraman et al, 2012;Hossain, 2021), so again it suggests that solid diffusivity has influence on voltage hysteresis.…”
Section: Impact Of Sensitivity Analysissupporting
confidence: 54%
See 1 more Smart Citation
“…In case of ๐›บ, constant values were used throughout the lithiation-delithiation cycling. Some impacts from ๐›บ were seen, but this parameter is also connected with diffusivity as reported by various researchers at their work (Verbrugge et al, 2015;Verbrugge and Cheng, 2019;Sethuraman et al, 2010;Sethuraman et al, 2012;Hossain, 2021), so again it suggests that solid diffusivity has influence on voltage hysteresis.…”
Section: Impact Of Sensitivity Analysissupporting
confidence: 54%
“…Here, ๐œŽ โ„Ž ฮฉ is called the stress induced voltage. Cheng and Verbrugge (2018), Jin et al (2019) and Hossain (2021) and Zhang et al (2007) all indicated how important it is to include this additional term in BV equation. ๐‘– 0 is called the exchange current density.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…We studied different types of reports/models/data sheets such as medical, mathematical, simulation, experimental, statistical, economical, engineering, socio economic etc. (Hossain, 2021;Cousens et al, 2011;Pedicelli et al, 2022;Hossain et al, 2020a;Fiorentino et al, 2018;Morshed et al, 2019;Hossain et al, 2020b;Romanenko et al, 2022;Pereira et al, 2019;Hossain et al, 2022a;Lobstein et al, 2019;Quek et al, 2017;Hossain et al, 2022b;Park et al, 2012;Inchley et al, 2020;Masud et al, 2021;Wijnhoven et al, 2014;van Ekris et al, 2016;Hossain, 2020;Waters et al, 2011;Homer et al, 2019;Hossain and Kim, 2020;Rutter et al, 2017;Finegood et al, 2010;Hossain, 2023;Savona et al, 2021;Malik et al, 2013;Idris et al, 2023;Monzani et al, 2019). We tried to figure out what would be the best-suited model/report to represent our investigation.…”
Section: Statistical Report Generationmentioning
confidence: 99%